2021
DOI: 10.1038/s41598-021-82994-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery corrects N-acetylglutamate synthase deficiency and enables insights in the physiological impact of L-arginine activation of N-acetylglutamate synthase

Abstract: The urea cycle protects the central nervous system from ammonia toxicity by converting ammonia to urea. N-acetylglutamate synthase (NAGS) catalyzes formation of N-acetylglutamate, an essential allosteric activator of carbamylphosphate synthetase 1. Enzymatic activity of mammalian NAGS doubles in the presence of L-arginine, but the physiological significance of NAGS activation by L-arginine has been unknown. The NAGS knockout (Nags−/−) mouse is an animal model of inducible hyperammonemia, which develops hyperam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…However, the only curative treatment is liver transplantation. Interestingly, gene therapy based on rAAV administered to adult mice has proven to improve lifespan, weight gain and some biochemical parameters in several UCD mouse models, namely for deficiencies of OTC [ 24 , 25 ], ARG1 [ 24 ], CPS1 [ 27 ], NAGS [ 40 ], ASA [ 41 , 42 ] and CTLN1 [ 34 , 35 ]. Moreover, a phase 1/2 clinical trial based on rAAV administration to treat late onset OTC in adults has shown significant therapeutic results (NCT02991144, NCT03636438), leading to the prompt initiation of an ongoing phase 3 randomized, double-blind, placebo-controlled cross-over clinical trial (NCT05345171).…”
Section: Discussionmentioning
confidence: 99%
“…However, the only curative treatment is liver transplantation. Interestingly, gene therapy based on rAAV administered to adult mice has proven to improve lifespan, weight gain and some biochemical parameters in several UCD mouse models, namely for deficiencies of OTC [ 24 , 25 ], ARG1 [ 24 ], CPS1 [ 27 ], NAGS [ 40 ], ASA [ 41 , 42 ] and CTLN1 [ 34 , 35 ]. Moreover, a phase 1/2 clinical trial based on rAAV administration to treat late onset OTC in adults has shown significant therapeutic results (NCT02991144, NCT03636438), leading to the prompt initiation of an ongoing phase 3 randomized, double-blind, placebo-controlled cross-over clinical trial (NCT05345171).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid Prom‐Ex1‐Int1‐Luc (Sonaimuthu et al, 2021) was a template for the introduction of the NM_153006.2:c.427‐222G>A and NM_153006.2:c.427‐218A>C sequence changes. Mutagenic primers 5ʹ‐CCGACCTTGGATTCCGGGACATCTTTGGGGG‐3ʹ and 5ʹ‐CCCCCAAAGATGTCCCGGAATCCAAGGTCGG‐3ʹ were used to generate the c.427‐222G>A sequence change while primers 5ʹ‐TCCCTCCGACCTGGGACTCCGGGAC‐3ʹ and 5ʹ‐GTCCCGGAGTCCCAGGTCGGAGGGA‐3ʹ were used for the c.427‐218A>C sequence change.…”
Section: Methodsmentioning
confidence: 99%
“…Culturing of the HepG2 cells (ATCC) and the HuH‐7 cells (Charles Rice laboratory, Rockefeller University), their transfections, and reporter assays were carried out as described previously (Sonaimuthu et al, 2021; Williams et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations